Answer:
The solution of the equation is
⇒ 3rd answer
Explanation:
* Lets explain how to solve this problem
- The function f(x) = e^x is called the (natural) exponential function
- The natural logarithm (㏑), or logarithm to base e, is the inverse
function to the natural exponential function
∵
is an exponential function
∴ We can solve it by using the inverse of e (㏑)
- Remember:
#
![ln(e)=1](https://img.qammunity.org/2020/formulas/mathematics/high-school/x54djqahe34qp1x1mdc1qkdxtf2q7bnhyk.png)
#
![ln(e^(m))=m(ln(e))=m](https://img.qammunity.org/2020/formulas/mathematics/high-school/g3xwu73qq6c99wipiu7sl39cd33mg5l8gk.png)
- Insert ln in both sides
∴
![ln(e^(2x+5))=ln(4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/mqs5sxa7lvy2omluz9i5tvbefwbqfrgdb0.png)
∵
![ln(e^(2x+5))=(2x+5)ln(e)=2x+5](https://img.qammunity.org/2020/formulas/mathematics/high-school/c9kd0adxwl7k75xyowd309g84ipu3g9ba0.png)
∴ 2x + 5 = ㏑(4)
- Subtract 5 from both sides
∴ 2x = ㏑(4) - 5
- Divide both sides by 2 to find x
∴
![x=(ln(4)-5)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ksantpu6ftudtzp9i5k6nr3z6ybpbologc.png)
* The solution of the equation is
![x=((ln4)-5)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ph1acc5xe66dd1d106jrdxiys3f67fgikz.png)